Mitochondrial fusion and fission: The fine-tune balance for cellular homeostasis - Adebayo, Mary; Singh, Seema; Singh, Ajay Pratap; Dasgupta, Santanu (The FASEB journal, 2021)
Mitochondria are highly dynamic, maternally inherited cytoplasmic organelles, which fulfill cellular energy demand through the oxidative phosphorylation system. Besides, they play an active role in calcium and damage-associated molecular patterns signaling, amino acid, and lipid metabolism, and apoptosis. Thus, the maintenance of mitochondrial integrity and homeostasis is extremely critical, which is achieved through continual fusion and fission. Mitochondrial fusion allows the transfer of gene products between mitochondria for optimal functioning, especially under metabolic and environmental stress. On the other hand, fission is crucial for mitochondrial division and quality control. The imbalance between these two processes is associated with various ailments such as cancer, neurodegenerative and cardiovascular diseases. This review discusses the molecular mechanisms that control mitochondrial fusion and fission and how the disruption of mitochondrial dynamics manifests into various disease conditions.Mitochondria are highly dynamic, maternally inherited cytoplasmic organelles, which fulfill cellular energy demand through the oxidative phosphorylation system. Besides, they play an active role in calcium and damage-associated molecular patterns signaling, amino acid, and lipid metabolism, and apoptosis. Thus, the maintenance of mitochondrial integrity and homeostasis is extremely critical, which is achieved through continual fusion and fission. Mitochondrial fusion allows the transfer of gene products between mitochondria for optimal functioning, especially under metabolic and environmental stress. On the other hand, fission is crucial for mitochondrial division and quality control. The imbalance between these two processes is associated with various ailments such as cancer, neurodegenerative and cardiovascular diseases. This review discusses the molecular mechanisms that control mitochondrial fusion and fission and how the disruption of mitochondrial dynamics manifests into various disease conditions.